Obvezni izvod serijskih publikacij v Narodni in univerzitetni knjižnici - Kalčič, Dunja (Knjižnica, 2007)
The article outlines the socio-historic circumstances related to the emergence and development of serial publications, their properties and characteristics affecting the specificities of the collection and storage of legal deposit copies. Short description of the history of legal deposit on Slovenian territory is followed by a numerical survey of legal deposit copies in the years 1948-2006. It is expected that the new Legal Deposit Act will enable more regular and thorough inflow of legal deposit copies of serial publications in National and University Library.
Keywords: obvezni izvod; serijske publikacije; Narodna in univerzitetna knjižnica; National and University Library of Slovenia; Ljubljana; zgodovinski pregledi